2021
DOI: 10.21203/rs.3.rs-1014162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Electronic Acupuncture At A Specific Frequency In Facilitating The Passage of NGF Through The Blood-Brain Barrier And Its Effect On Learning And Memory In MCAO/R Rats

Abstract: The blood-brain barrier (BBB) maintains the balance of the internal environment of the brain and strictly controls substance exchange between the brain and blood dynamically but stably. Transient increases in the permeability of the BBB plays an important role in helping macromolecular drugs enter the brain to exert their pharmacological effects. Previous research has revealed that electronic acupuncture (EA) stimulation at a specific frequency can enhance the permeability of the BBB and induce the entry of 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It was also found that EA at GV20 and Shuigou (GV26) enhanced the permeability of the blood-brain barrier in the prefrontal cortex and induced the uptake of NGF by prefrontal neurons (156). Nape cluster acupuncture has neuroprotective and restorative effects in rats with post-ischemic stroke sequelae, and its mechanism may involve effective upregulation of BDNF and NGF protein expression (157).…”
Section: Acupuncture For Enhancing Factorsmentioning
confidence: 99%
“…It was also found that EA at GV20 and Shuigou (GV26) enhanced the permeability of the blood-brain barrier in the prefrontal cortex and induced the uptake of NGF by prefrontal neurons (156). Nape cluster acupuncture has neuroprotective and restorative effects in rats with post-ischemic stroke sequelae, and its mechanism may involve effective upregulation of BDNF and NGF protein expression (157).…”
Section: Acupuncture For Enhancing Factorsmentioning
confidence: 99%
“…A fixed frequency of 2 or 100 Hz may show easy adaptability and a relatively continuous and stable stimulation, which may reduce the effect of EA [143]. Therefore, 2/100 Hz EA was applied to the GV20 and GV26 acupoints for 40 min, effectively increasing BBB permeability in rats [144]. However, for hippocampal synaptic transmission, high-frequency EA could demonstrate a better effect in rats with Alzheimer's disease [145].…”
Section: How To Improve the Effect Of Acupuncturementioning
confidence: 99%
“…Acupuncture can upregulate vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor 2 (VEGFR2), basic fibroblast growth factor (bFGF), and CD34 + , thereby promoting the proliferation of vascular endothelial cells, increasing local cerebral blood flow, activating multiple signaling pathways, and mediating vascular and nerve regeneration [158]. EA stimulation of "Baihui" (GV20) and "Shuigou" (GV26) at a specific frequency has been reported to increase the permeability of BBB, providing a strategy for the treatment Oxidative Medicine and Cellular Longevity of nervous system diseases [143,144]. Liu et al [111] found that EA could regulate the expression of VEGF genes and promote angiogenesis in the ischemic cerebral cortex, which may play an important role in the improvement of CI in ischemic stroke.…”
Section: Vascular-glia-neuron Unit Might Be Amentioning
confidence: 99%